Warrant and grant issued to Robert Still - Still, Robert
Warrant (1802 January 10) and grant (1805 September 26) issued to Still by the Georgia surveyor general for land in Hancock County, Ga.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Georgia. -- Surveyor General Department; Land grants -- Georgia -- Hancock County